A global model for the estimation of transport costs. Issue 1 (1st January 2020) - Camisón-Haba, Sergio; Clemente-Almendros, Jose A.
Abstract: This paper presents a model of transport cost determinants that corrects the specification problems observed in the transport cost equations in previous literature. The model includes freight transport supply and demand, as well as infrastructure quality and non-time-varying fixed effects related to the route, the exporting company, its strategy and the product. In addition, when defining the origin-destination routes, the model more appropriately accounts for economies of network and economies of scale. In order to build the database, 583 personal interviews were conducted over the course of 2011 with producing companies that ship goods and with the logistics operators. As a result, 305 routes between the Valencian Community and Europe were identified, from which 6390 observations were obtained. The results show that distance is a determining factor in the cost of transport, notwithstanding the infrastructure coverage and improvements in quality. At the same time, the analysis confirms that transport cost is more sensitive to the degree of competition on the route, the volume of freight on the route and the volume of goods shipped on the route by the exporting company, the configuration of the supply chain, the company strategy and the coverage and quality of transport infrastructure.